Richard Dyer-Bennet : The Last Minstrel - Jenkins, Paul O. (Book collections on Project MUSE., 2010)
In the 1940s and '50s, Richard Dyer-Bennet (1913-1991) was among the best known and most respected folk singers in America. Paul O. Jenkins tells, for the first time, the story of Dyer-Bennet, often referred to as the "Twentieth-Century Minstrel." Dyer-Bennet's approach to singing sounded almost foreign to many American listeners. The folk artist followed a musical tradition in danger of dying out. The Swede Sven Scholander was the last European proponent of minstrelsy and served as Dyer-Bennet's inspiration after the young singer traveled to Stockholm to meet him one year before Scholander's